Dimensi Hukum Komunikasi Dalam Pelayanan Rumah Sakit: Suatu Perspektif Medikolegal - Muhammad Luthfie Hakim (Kertha Wicaksana, 2026)
Communication in healthcare is not merely a technical or interpersonal issue, but rather an integral part of the legal and ethical responsibilities of the medical profession. This article aims to examine the legal aspects of communication in hospitals through a normative and analytical approach. The discussion focuses on the classification of communication types (clinical and administrative), effective communication methods (SBAR and closed-loop), and the strategic role of medical records in documenting explanations and informed consent for medical procedures. By examining the provisions of Law Number 17 of 2023 concerning Health, relevant ministerial regulations, and field practice, this article demonstrates that communication and documentation failures are among the main causes of medical disputes in Indonesia. The article also identifies common documentation errors, such as incomplete information, undocumented explanations, or explanations provided by unauthorized parties. The article concludes that effective and well-documented communication not only protects patient rights but also strengthens the legal standing of medical personnel and hospitals. Reforming communication and documentation systems in healthcare facilities should be an integral part of strategies to improve quality and provide legal protection in medical practice.